Hungary : Report on Observance of Standards and Codes; Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2007)
This report provides an assessment of fiscal transparency practices in Hungary in relation to the requirements of the IMF Code of Good Practices on Fiscal Transparency. The report reveals that Hungary has increased its level of transparency in a number of areas since the last fiscal Report on the Observance of Standards and Codes in 2001. In particular, the coverage of fiscal reporting and the budget has been considerably extended. Fiscal reporting now covers virtually all of general government.